2020
DOI: 10.1186/s12879-020-05354-3
|View full text |Cite
|
Sign up to set email alerts
|

The effects of family, society and national policy support on treatment adherence among newly diagnosed tuberculosis patients: a cross-sectional study

Abstract: Background: Non-adherence to tuberculosis (TB) treatment is the most important cause of poor TB outcomes, and improving support for TB patients is a primary priority for governments, but there has been little research on the effects of family, social and national policy support factors on TB treatment adherence. The current study evaluated treatment adherence among newly diagnosed TB patients in Dalian, northeastern China, and determined the effects of family, society, and national policy support factors on tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 47 publications
1
24
1
1
Order By: Relevance
“…In Xizang, large families live together in multi-generational households and all participants discussed their families as providing social support in relation to their care. Other studies in Xizang, as well as other areas of China, have highlighted the importance of social and family support in TB care on adherence, particularly amongst newly diagnosed patients [ 26 , 64 ]. A 2014 review reported that family treatment observation combined with health worker home visits, as in our setting, can achieve high cure rates if overall treatment is closely monitored and well-connected to the healthcare system [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Xizang, large families live together in multi-generational households and all participants discussed their families as providing social support in relation to their care. Other studies in Xizang, as well as other areas of China, have highlighted the importance of social and family support in TB care on adherence, particularly amongst newly diagnosed patients [ 26 , 64 ]. A 2014 review reported that family treatment observation combined with health worker home visits, as in our setting, can achieve high cure rates if overall treatment is closely monitored and well-connected to the healthcare system [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are five family functions: The affective function, socialization, social placement function, the health-care function, the reproductive function, and the economic function [36]. It has always been recommended that medical professionals, patients and family members medication management be strengthened and that budgetary funding for enhancing commitment be increased [37]. Therefore, in realizing adequate health service facilities to control pulmonary TB, it is necessary to provide quality health services such as health counseling rooms [38].…”
Section: Counter Measurement Of Pulmonary Tbmentioning
confidence: 99%
“…Many studies have reported on factors that influence adherence to TB treatment, including age, employment, and lifestyle choices, such as consuming alcohol [46], [47]. Other intrinsic factors that influence treatment adherence are knowledge about TB [47], [48], [49], including drug side effects and having a positive self-image and self-awareness [50]. In contrast to adherence, a factor that influences nonadherence to TB treatment is the side effects of the medication.…”
Section: Antecedentsmentioning
confidence: 99%
“…External factors that influence adherence to TB treatment consist of three aspects: family and social environment, health professionals, and policy. Support comes from family members, including family members that supervise TB medication frequently and provide spiritual encouragement [48]. Encouragement provided by family members can increase patient confidence in adhering to treatment.…”
Section: Antecedentsmentioning
confidence: 99%
See 1 more Smart Citation